Problems in root canal obturation. Lateral compaction of cold gutta-percha (LLC "Endo Press", 2020)
The article deals with sequential technology of root canal obturation by lateral compaction of cold gutta-percha and prophylaxys of such complications as vertical cracks and fractures.